2015
DOI: 10.3109/03008207.2015.1069285
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of the effects of heparin and the direct factor Xa inhibitor, rivaroxaban, on bone microstructure and metabolism in adult rats

Abstract: Rivaroxaban leads to fewer adverse effects on bone microstructure than heparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
6
0
2
Order By: Relevance
“…In our previous study, it was found that unfractionated heparin had a more marked adverse effect on bone microstructure and function, compared with rivaroxaban (9). The present study showed that rivaroxaban inhibited the expression of FGF2, whereas unfractionated heparin repressed the expression of HPSE and FGF2.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In our previous study, it was found that unfractionated heparin had a more marked adverse effect on bone microstructure and function, compared with rivaroxaban (9). The present study showed that rivaroxaban inhibited the expression of FGF2, whereas unfractionated heparin repressed the expression of HPSE and FGF2.…”
Section: Discussionsupporting
confidence: 50%
“…The overexpression of HPSE and FGF2 overcame the adverse effects of unfractionated heparin and rivaroxaban. In our previous study, it was found that treatment with unfractionated heparin and rivaroxaban for 4 weeks had negative effects on bone microstructure and function in adult rats (9). Therefore, the results of the present in vitro study suggested that the negative effects of long-term treatment with unfractionated heparin or rivaroxaban on bone health were due to their ability to inhibit the growth of osteoblasts.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Since Heparin and LWMH effects are dose dependent we used the maximum dose in order to have clear and obvious results. Resent study 28 for the effects of Heparin and Rivaroxaban on bone microstructure and metabolism (bone quality and quantity) found that Rivaroxaban leads to fewer adverse effects on bone.…”
Section: Discussionmentioning
confidence: 99%
“…Συγκεκριμένα υπάρχουν ενδείξεις ότι το Rivaroxaban δεν επηρεάζει την διαδικασία της οστικής επούλωσης [85][86][87] και την επιμετάλλωση των οστικών κυτάρων 86 . Τούτο πιθανότατα οφείλεται στην παροδική δράση του Rivaroxaban στα οστικά κύτταρα και στην προσαρμογή των κυττάρων και την αντισταθμιστική του δράση μέσω άλλων μηχανισμών 85,86,[88][89][90][91] . Στο αντικείμενο όμως που υπάρχει παντελής έλλειψη δημοσιεύσεων και μελετών για όλα τα νεότερα από του στόματος αντιπηκτικά και ειδικότερα για το Rivaroxaban είναι για την επίδρασή του στην οστεοενσωμάτωση των υλικών και προθέσεων που χρησιμοποιούνται στην καθημερινή ορθοπαιδική χειρουργική πράξη ταυτόχρονα με την χορήγηση αντιπηκτικών.…”
Section: R I V a R O X A B A N ( X A R E L T O )unclassified